Content-specific noticing: A large-scale survey of mathematics teachers' noticing. (May 2021) - Copur-Gencturk, Yasemin; Rodrigues, Jessica
Abstract: Teachers' noticing is an important skill for learning from and improving their teaching. We investigated what teachers noticed in short video clips of a real classroom teacher's interaction with students around a mathematics problem by collecting data from 496 U.S. fourth- and fifth-grade teachers from 48 states. Our analyses indicated that 67.5% of teachers' responses focused on content-specific teaching and learning events, whereas 14% of them attended to the content-specific issues at the heart of students' confusion. In-depth analyses of 5300 teachers' responses showed that the teachers noticed and analyzed teaching-related issues from a wide range of angles. Highlights: The majority of teachers noticed and analyzed content-specific teaching and learning issues. Few teachers noticed the key teaching and learning issues that led to students' confusion. Teachers noticed teaching-related issues in a wide range of areas such as use of probing questions. Teachers noticed student-related issues in three areas: engagement, ability, and understanding.